The effect of CASP3 rs4647610 and rs4647602 polymorphisms on tumour size and cancer stage in papillary thyroid carcinoma. Issue 3 (2nd July 2020) - Heidari, Z; Eskandari, M; Aryan, A; Rostamzad, F; Salimi, S
ABSTRACT: Background: Papillary thyroid carcinoma (PTC) is the most frequent form of thyroid cancer whose incidence has increased in recent years. Dysregulated apoptosis is known in the pathogenesis of various cancers. Caspase-3 is an important apoptotic component and its abnormal function may play a key role in cancer pathogenesis. We tested the hypothesis of a link between CASP3 single nucleotide polymorphisms rs4647610 and rs4647602 on PTC and its clinical outcomes. Material and methods: A total of 134 PTC patients and 151 healthy controls were genotyped for CASP3 rs4647610 and rs4647602 single nucleotide polymorphisms (SNPs) using PCR-RFLP method. Results: Allele and genotype frequencies of both SNPs were not different between cases and controls. The combined genotypes and haplotypes were not linked to PTC. However, the frequencies of CASP3 rs4647610 GA and AA genotypes were higher in PTC patients with larger tumour size (≥1 cm), and the rs4647610 SNP was associated with increased tumour size in the dominant model (OR 3.4 [95% CI, 1.1–11], P = 0.04). The CASP3 rs4647602CA and AA genotypes were higher in PTC patients with lower TNM stage (I–II) compared to higher stages (III–IV). No association was observed between CASP3 polymorphisms and other PTC outcomes. Conclusion: Although CASP3 rs4647610 and rs4647602 SNPs are not associated with PTC, rs4647610 is linked to larger tumour size, and rs4647602 to lower stage of cancer.